Smallholder aquaculture diversifies livelihoods and diets thus improving food security status: evidence from northern Zambia - Kaminski, A.M.; Cole, S.M.; Johnson, J.; Thilsted, Shakuntala H.; Lundeba, M.; Genschick, S.; Little, David C. (Springer, 2024)
Much has been made of the potential for aquaculture to improve rural livelihoods and food and nutrition security in Africa, though little evidence exists to back such claims. This study, conducted in northern Zambia, assessed the benefits of adopting aquaculture by comparing a sample of households with (n = 177) and without fishponds (n = 174).